PENGARUH PENILAIAN PRESTASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI (Studi Pada Unit Pelaksana Teknis Pendidikan Kecamatan Sumbersari Kabupaten Jember) - Ratna Dwi Arini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Purpose of this research was to observe the influence of performance appraisal which consists of the aspects are assessed, appraiser, methods of appraisal and feedback that influence employee satisfaction Technical Implementation Unit (UPT) Education Sumbersari District of Jember, simultaneously or partially. To determine the influence of the dependent variable (job satisfaction) of the independent variable (performance appraisal) used multiple linear regression analysis with analysis method F test and t test. This kind of research is explanatory research, to describes the connected and the influence of some variables that have been defined. The population at the same time the study sample was 50 employees Technical Implementation Unit (UPT) Education Sumbersari District of Jember, and also called the census sample. The results using multiple linear regression analysis showed that there is significant influence between variables simultaneously Aspects are Assessed (X1), Appraiser (X2), Methods of Apprasal (X3), Feedback (X4) on Employee Job Satisfaction (Y) Unit Technical Implementation (UPT) Education Sumbersari District of Jember, with a significance level of 0.000 and determination coefficient of 0.594 (59.4%). While partially through t test known that, just Variable Appraisers (X2) showed a value 3.597 with significant 0.001 and also Variables Method of Appraisal (X3) showed a value 1.954 with significant 0.057 which indicates partial significant influence on employee job satisfaction (Y). Through this research, it is expected that the Technical Implementation Unit (UPT) Education Sumbersari District of Jember to fix implementation of performance appraisal, so as to improve employee satisfaction.Keywords: Job Performance Appraisal, Aspects Are Assessed, Method Of Appraisal, Appraiser, Feedback, Employee Job Satisfaction, Technical Implementation Unit (UPT) Education Sumbersari District of Jember.